Foreword - Cox, James D. (1997)
This thesis addresses the issues of (inter)harmonics propagation on electrical grids. More specifically it concerns two different kinds of studies. The first one is the harmonic impact of the integration of new technologies such as Electric Vehicle charging parks which generate harmonic voltages. The second one is the propagation on these grids of communication signals such as the pricing signal. These two kinds of voltages behave a priori the same way since they are superimposed to the fundamental feeding voltage, with a higher frequency. However, their main structural difference is that, while harmonic voltages generated by electric cars are unwanted on electrical grid, the pricing signal is intended at certain points of the grid. For the first kind of studies, concerning harmonics generated by Electric Vehicles, the aim of this project was to determine the problems that may appear on electrical grids when electric car parks are connected thereto. To do so, laboratory measurements on several Electric Vehicle models, separately or simultaneously, were performed. From their results, different models of EVs have been drawn up enabling to perform simulations on an existing car park. Some measurements were then carried out on this car park in order to conclude on its impact on the Power Quality of the grid. The second study is about the pricing signal propagation. It focuses on different ways of modeling grid components, especially loads, in simulation tools at the specific frequency of this signal. For Medium Voltage grids, several load models can be found in the literature and are compared in this report. For Low Voltage grids, a model based on the results of recent measurements is suggested in the report